2006
DOI: 10.7748/ns2006.05.20.38.46.c4165
|View full text |Cite
|
Sign up to set email alerts
|

Using the Liverpool Care Pathway for a dying patient

Abstract: This article describes the experience of staff in one acute hospital in Northern Ireland who adapted the Liverpool Care Pathway (LCP) for the dying patient to suit their organisation. It focuses on one patient's journey, from diagnosis to terminal care. The patient remained on the care pathway for 12 days. This reflection demonstrates that, as long as patients continue to meet the criteria for the LCP, some may be on the care pathway for more than the recognised average of two days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It is evident from reviewing existing literature that nurses have engaged in EOLC pathway development, either as members of quality improvement teams (Bookbinder al. 2005al. , McNicholl et al 2006, multidisciplinary committees, steering groups and working parties (Pooler et al 2003, Luhrs et al 2005, Mirando et al 2005, Jackson et al 2009, Lo et al 2009 or as specialist palliative care practitioners (Lhussier et al 2007).…”
Section: Nursingõs Contribution To the Evolution Of End-oflife Care Pmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident from reviewing existing literature that nurses have engaged in EOLC pathway development, either as members of quality improvement teams (Bookbinder al. 2005al. , McNicholl et al 2006, multidisciplinary committees, steering groups and working parties (Pooler et al 2003, Luhrs et al 2005, Mirando et al 2005, Jackson et al 2009, Lo et al 2009 or as specialist palliative care practitioners (Lhussier et al 2007).…”
Section: Nursingõs Contribution To the Evolution Of End-oflife Care Pmentioning
confidence: 99%
“…Effective EOLC pathway implementation is contingent on a practitioner-led, strategic approach in which a supportive space is created, enabling the voices of those who will use pathways to be heard. Analysis of the literature revealed that several small scale, international studies, audits and anecdotal accounts have described, in various detail, EOLC pathway implementation for various conditions and in different care settings (Fowell et al 2002, Jack et al 2004, Luhrs et al 2005, McNicholl et al 2006). Frequently quality improvement methodologies were advocated and have been used to facilitate EOLC pathway implementation (Ellershaw et al 1997, Bookbinder et al 2005.…”
Section: Implementing End-of-life Care Pathwaysmentioning
confidence: 99%
“…It is usually only used in the patient's last few days and ensures that the whole team record their notes in one place and gives guidance for continuing assessment of the patient [22]. The effect of the LCP in the Netherlands has been studied and was found to improve documentation and that, with symptoms also controlled better, it improved care for people who were dying [23].…”
Section: Initiatives To Improve Quality Of Palliative Carementioning
confidence: 99%
“…LCP is a protocol dealing with the last moments (about 48 hours, in some modifications up to even 12 days) of the patient's life [4,19]. It only requires from the medical professionals ticking the right option on the form or choosing one out of two one-letter codes.…”
Section: Elements Of the End-of-life Care Included In The Protocol (Omentioning
confidence: 99%
“…The needs of both the patient and his family are included. Limiting the number of unnecessary and painful medical procedures was the goal [1][2][3][4][5]. Protocols resembling the LCP have been in use in the British health care system for years, facilitating work and eliminating the personnel's mistakes [1].…”
Section: What Is the Liverpool Care Of Dying Pathway?mentioning
confidence: 99%